2019
DOI: 10.1016/j.beproc.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Costly curiosity: People pay a price to resolve an uncertain gamble early

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…For example, blockade of D1/D5 dopaminergic receptors during exploration of novel environments decreases the consolidation of new spatial maps [66], suggesting a causal link between exploration-triggered dopamine and memory consolidation. Also consistent with the idea that curiosity triggers enhanced information seeking, several studies have shown how nonhuman primates and humans have a strong preference for advance information-seeking [14,20,[69][70][71]. That is, if individuals have the possibility of receiving advance information about the value of an upcoming reward, they have a strong bias to select the advance information even if this option is associated with sacrificing parts of the reward.…”
Section: Curiosity Triggers Dopaminergic Neuromodulationmentioning
confidence: 62%
“…For example, blockade of D1/D5 dopaminergic receptors during exploration of novel environments decreases the consolidation of new spatial maps [66], suggesting a causal link between exploration-triggered dopamine and memory consolidation. Also consistent with the idea that curiosity triggers enhanced information seeking, several studies have shown how nonhuman primates and humans have a strong preference for advance information-seeking [14,20,[69][70][71]. That is, if individuals have the possibility of receiving advance information about the value of an upcoming reward, they have a strong bias to select the advance information even if this option is associated with sacrificing parts of the reward.…”
Section: Curiosity Triggers Dopaminergic Neuromodulationmentioning
confidence: 62%
“…Research on curiosity is generally concerned with psychological and computational mechanisms underlying information-seeking behavior, especially when information bears no implications for acquiring extrinsic rewards (Gottlieb & Oudeyer, 2018). Research has shown that humans (and animals) often prefer acquiring information even if the information is not instrumental to earn rewards (e.g., Bennett, Bode, Brydevall, Warren, & Murawski, 2016;Blanchard, Hayden, & Bromberg-Martin, 2014;Bromberg-Martin & Hikosaka, 2009;Brydevall, Bennett, Murawski, & Bode, 2018;FitzGibbon, Komiya, & Murayama, 2020;Lanzetta & Driscoll, 1966;Rodriguez Cabrero, Zhu, & Ludvig, 2019;Wang & Hayden, 2019;Wyckoff Jr, 1952; see also Grant, Kajii, & Polak, 1998).…”
Section: Research On Curiosity and Reward Learning Models Of Information Seekingmentioning
confidence: 99%
“…This article is intended solely for the personal use of the individual user and is not to be disseminated broadly. nès, Woodford, & Gottlieb, 2019;Rodriguez Cabrero, Zhu, & Ludvig, 2019;van Lieshout, Vandenbroucke, Müller, Cools, & de Lange, 2018;Vasconcelos, Monteiro, & Kacelnik, 2015), even though this leads to a reduction in future expected reward. In humans, there is marked heterogeneity in the strength of this preference (Bennett et al, 2016), suggesting individual differences in aversion to uncertainty that resemble those proposed in theories of obsessive-compulsion and anxiety (Krohne, 1993;Sorrentino et al, 1990).…”
mentioning
confidence: 99%
“…This behavior is also unconfounded by threat overestimation or risk aversion, since these confounds are induced by the instrumentality of information. Previous research has shown that humans and other animals behave as though noninstrumental information has an intrinsic value, and will even pay an explicit cost (such as a monetary cost, a wait-time cost, or foregone primary reward) to acquire it (Bennett et al, 2016; Blanchard, Hayden, & Bromberg-Martin, 2015; Bromberg-Martin & Hikosaka, 2009, 2011; Brydevall et al, 2018; Charpentier, Bromberg-Martin, & Sharot, 2018; Iigaya, Story, Kurth-Nelson, Dolan, & Dayan, 2016; Kobayashi, Ravaioli, Baranès, Woodford, & Gottlieb, 2019; Rodriguez Cabrero, Zhu, & Ludvig, 2019; van Lieshout, Vandenbroucke, Müller, Cools, & de Lange, 2018; Vasconcelos, Monteiro, & Kacelnik, 2015), even though this leads to a reduction in future expected reward. In humans, there is marked heterogeneity in the strength of this preference (Bennett et al, 2016), suggesting individual differences in aversion to uncertainty that resemble those proposed in theories of obsessive-compulsion and anxiety (Krohne, 1993; Sorrentino et al, 1990).…”
mentioning
confidence: 99%